Characteristics of Indigenous Bacterial Isolates from Cocoa Plantations in Meko Village, Central Sulawesi, with Ability to Degrade Cellulose - Shchegolkova, Nataliya; Kalimutu, Putu Krisnawan; Wirawan, I Gede Putu; Suada, I Ketut (International Journal of Biosciences and Biotechnology; Vol 11 No 2 (2024): International Journal of Biosciences and BiotechnologyDO - 10.24843/IJBB.2024.v11.i02.p06, 2024)
Indonesia is the third largest cocoa bean producing country in the world after Ghana and the Ivory Coast with current Indonesian cocoa bean production of 600,000 tons per year. The quality of cocoa is still relatively low compared to the harvest potential that should be obtained, such as the Sulawesi III clone which provides a yield potential of 2-2.4 tons per hectare. This study aims to obtain indigenous bacteria from Meko village so that the role of each bacteria can be further investigated. The results of growing bacteria on LB media found 25 isolates which were observed to have quite varied morphology including round and irregular shapes, having rough and dull and slimy surfaces, opaque, cloudy and colored (yellow and reddish) and having flat and rising elevations. Most of the bacteria obtained were rod-shaped, namely 23 were gram negative and three were gram positive. The shape of the cell is dominated by the shape of the rod, about 19 are rod-shaped and the remaining six are round.